Presence of predatory nematode (Nematoda, Mononchidae) in a Wilson's storm petrel nest, Oceanites oceanicus (Ave, Procellariiformes, Hydrobatidae), in Southern Shetland Islands, Antarctica. - Camino, Nora Beatriz; Archuby, Diego Ignacio; Montalti, Diego; González, Sandra Elizabeth
The discovery of a mononchid nematode in the Argentinean Antarctic turns out to be a first citation of this predatory nematode in a Wilson's storm petrel nest. In that nest there were dead young petrels that we deduced full of bacteria, the bacteriophage nematodes went to the nest to feed in the cadavers and were followed by their predatory nematodes. We found a free soil predatory nematode Coomansus jairajpuri (Nematoda, Mononchida) in a Wilson's storm petrel nest, Oceanites oceanicus (Ave, Procellariiformes, Hydrobatidae), in Southern Shetland Islands, Antarctica. Working on reproductive biology of this bird and during the analysis of the material used for the construction of the nest, we observed, on January of 2011, the presence of specimens of free living nematodes. The nematode specimens were fixed in 4 parts 40% formalin and then put in TAF pure. We can diagnose our species that differed from the others by having the dorsal tooth apex at 75% of buccal cavity length from its base and has 14 supplements, most of them mammiliform and few are low mounds. We are waiting for a new campaign to the Argentinean antarctic to find more nematodes to identify the species; we need more number of specimens to describe this species as we suspect it is a new one. Fil: Camino, Nora Beatriz. Provincia de Buenos Aires. Gobernación. Comisión de Investigaciones Científicas; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Estudios Parasitológicos y de Vectores. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Centro de Estudios Parasitológicos y de Vectores; Argentina Fil: Archuby, Diego Ignacio. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina Fil: Montalti, Diego. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo; Argentina. Consejo ...